Giant perivascular spaces causing hemiparesis successfully treated by cystoventriculoperitoneal shunt. (2nd January 2015) - Roelz, Roland; Egger, Karl; Reinacher, Peter
Abstract: We report a 55-year-old man affected by a slowly progressive hemiparesis. Imaging revealed giant dilations of brain perivascular spaces, or Virchow–Robin spaces of the thalamo-mesencephalic region and occlusive hydrocephalus. Stereotactic catheter cystoventriculostomy alone reverted hemiparesis. However, conversion of the catheter into a peritoneal shunt system was necessary to treat hydrocephalus.